A new approach to the determination of phosphate rock dissolution in organic soils using graphite furnace atomic absorption spectrophotometry - Hanafi, M.M.; Saifulbahari, A.R.; Peli, M. (Marcel Dekker Inc., 1996)
The determination of phosphorus (P) in 0.5M NaOH extracting solution following the dissolution of phosphate rock (PR) materials in mineral soils is frequently done using a molybdenum blue method. For organic soils, 0.5M NaOH soil extracts usually give dark color solutions. This dark color solution reduces the intensity of light in spectrophotometer, thus, underestimating the dissolution of PR in organic soils compared to mineral soils. A new approach using a graphite furnace atomic absorption spectrophotometer (GFAAS) was evaluated for measuring P in pure solutions; and this was used for measuring the dissolution of PR in organic soils. The P standard solutions prepared in distilled water, 1% humic acid, 1% fulvic acid, 0.5M NaOH, 0.5M NaOH+1% humic acid, and 0.5M NaOH+1% fulvic acid were used for establishing the standard curve and the selection of matrix modifier. The organic soils at different degree of decomposition (saprist, hemist, and fibrist) were incubated with gafsa phosphate rock (GPR), Christmas Island A‐grade phosphate rock (CIPR), and triple superphosphate (TSP) each at a rate of 0, 500, and 1000 mg P/kg soil. The dissolution of PR was measured using 0.5M NaOH‐extractable P and 0.5M BaC12/TEA‐extractable Ca. The measurement of peak area gave the highest sensitivity reading (p=0.01) compared to peak height; and lanthanum nitrate was the most suitable matrix modifier for determination of P in distilled water, 1% humic acid, 1% fulvic acid, 0.5MNaOH, 0.5MNaOH+l% humic acid, and 0.5M NaOH+1% fulvic acid. The dissolution of PR as measured by 0.5M NaOH decreases in the following sequence: Sapric (B) > Hemic > Fibric > Sapric (D). Absolute amounts of P increased with increasing levels of P addition; and TSP gave the highest dissolution value followed by GPR, and CIPR. The dissolution of PR in organic soils using 0.5M NaOH extracting solution can be accurately determined by GFAAS method.